Association between serum total bilirubin and diabetic kidney disease in US diabetic patients - Lv, Jian-Min; Shi, Xiu-E; Ma, Qiong; Chen, Nan; Fu, Mi; Liu, Jian-Zheng; Fan, Qiao-Rong (Frontiers in Endocrinology, 2023)
Background: Bilirubin has been widely reported to be a protective factor against diabetic kidney disease (DKD) in Asian populations. However, few large-sample analyses have been conducted in American populations. This study aimed to investigate the association between serum total bilirubin (STB) level and DKD in a US diabetic cohort.: This cross-sectional study enrolled participants from the National Health and Nutrition Examination Survey (NHANES) 2003-2018. Univariate and multivariate logistic regression analyses were performed to assess the association between STB level and DKD. Three models were conducted to control the potential confounding factors. Subgroup analysis was carried out for further validation.Results: Among the 5,355 participants, the median age [interquartile range (IQR)] was 62 [52-71] years; 2,836 (52.96%) were male, and 1,576 (29.43%) were diagnosed with DKD. In the entire cohort, no significant association between STB level and DKD was observed in any logistic regression models (p > 0.05). Subgroup analysis revealed that, in U.S. diabetic males, STB levels > 11.98 µmol/L were associated with a nearly 30% lower risk of DKD than STB levels ≤ 8.55 µmol/L. Additionally, a moderate STB level (8.56-11.98 μmol/L) was found associated with a nearly 25% lower risk of DKD in U.S. diabetic patients over 65 years old.The association of STB level with DKD may depict differences across diverse populations, among which the impact of race, sex, and age requires thorough consideration and relevant inferences should be interpreted cautiously.